2004
DOI: 10.1103/physrevb.70.195122
|View full text |Cite
|
Sign up to set email alerts
|

Phase diagram and magnetic collective excitations of the Hubbard model for graphene sheets and layers

Abstract: We discuss the magnetic phases of the Hubbard model for the honeycomb lattice both in two and three spatial dimensions. A ground state phase diagram is obtained depending on the interaction strength U and electronic density n. We find a first order phase transition between ferromagnetic regions where the spin is maximally polarized (Nagaoka ferromagnetism) and regions with smaller magnetization (weak ferromagnetism). When taking into account the possibility of spiral states, we find that the lowest critical U … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
88
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(96 citation statements)
references
References 26 publications
7
88
1
Order By: Relevance
“…Using the same procedure as above to fix U, we find that its value decreases as the size of the islands increase. The values of U so obtained are always below the critical value U ' 2:2t ' 5:5 eV above which infinite graphene would become antiferromagnetic [12,24].…”
mentioning
confidence: 99%
“…Using the same procedure as above to fix U, we find that its value decreases as the size of the islands increase. The values of U so obtained are always below the critical value U ' 2:2t ' 5:5 eV above which infinite graphene would become antiferromagnetic [12,24].…”
mentioning
confidence: 99%
“…Recent theoretical studies showed that intrinsic fer-romagnetism of graphene may exist [29,30,31], but it has not been observed so far. Room-temperature ferromagnetism was observed [32], but it was attribued to the presence of the defects on graphene.…”
Section: Introductionmentioning
confidence: 99%
“…However, since the DOS is very low, these peaks are small, and a very high (Hubbard) interaction is required to enter the DW regime. 10 The situation changes if we strongly dope graphene around the value μ ≈ |t|, where μ is the chemical potential and t ≈ 2.8 eV is the hopping parameter. The Fermi surface then acquires a hexagonal shape and nesting occurs in three directions (see Fig.…”
Section: Introductionmentioning
confidence: 99%